2022
DOI: 10.1029/2021wr030555
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of River Flow and Flood Dynamics by Existing and Planned Hydropower Dams in the Amazon River Basin

Abstract: Hydropower dams have received increased global attention due to their detrimental socioenvironmental ramifications. Such attention has led to an increase in studies on the impacts of reservoir operation on river flow; however, a holistic understanding of the compounded effects of hydropower dams on different hydrological characteristics is lacking, especially for large river basins such as the Amazon where hydropower development is on the rise. Here, we mechanistically quantify the historical impacts of existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Understanding how these changes may interact either synergistically or antagonistically is important for planning dams and navigation channels as well as regulating deforestation. Furthermore, although our estimates based on hydrologic-hydrodynamic modeling considered a natural basin scenario, without the effects of anthropogenic impacts such as dams (Chaudhari andPokhrel 2022, Flecker et al 2022), the impacts of rainfall changes on inundation extent reported here are well aligned with evidence from other, rainfallindependent remote sensing datasets. It is important to stress that such models have simplifications such as time-constant and rectangular river channel cross sections, which are necessary to be assumed due to scarcity of detailed, in situ data to be used in parameterization.…”
Section: Multiple Stressors Affecting Inundation Regimes In a Changin...supporting
confidence: 73%
See 2 more Smart Citations
“…Understanding how these changes may interact either synergistically or antagonistically is important for planning dams and navigation channels as well as regulating deforestation. Furthermore, although our estimates based on hydrologic-hydrodynamic modeling considered a natural basin scenario, without the effects of anthropogenic impacts such as dams (Chaudhari andPokhrel 2022, Flecker et al 2022), the impacts of rainfall changes on inundation extent reported here are well aligned with evidence from other, rainfallindependent remote sensing datasets. It is important to stress that such models have simplifications such as time-constant and rectangular river channel cross sections, which are necessary to be assumed due to scarcity of detailed, in situ data to be used in parameterization.…”
Section: Multiple Stressors Affecting Inundation Regimes In a Changin...supporting
confidence: 73%
“…If sustained in the future, the increase in maximum inundation extent observed across the central Amazon floodplains, driven by a change in rainfall regime, is unlikely to be the only change affecting floodplain inundation regimes. Human-driven hydrological changes in the basin that potentially affect river discharge and floodplain inundation include construction of hydropower dams (Chaudhari and Pokhrel 2022), the development of industrial waterways in the western Amazon tributaries that require dredging of river channels (AIDESEP 2019), and deforestation in both the uplands and floodplains (Castello et al 2013). Understanding how these changes may interact either synergistically or antagonistically is important for planning dams and navigation channels as well as regulating deforestation.…”
Section: Multiple Stressors Affecting Inundation Regimes In a Changin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The CaMa-Flood model combined with the H08 model has been used for several river basins globally (Boulange et al, 2021; C. M. R. Mateo et al, 2013). The CaMa-Flood model performs well in simulating flood dynamics (Chaudhari and Pokhrel, 2022;H. Dang et al, 2022;Gaur & Gaur, 2018;Hirabayashi et al, 2013Hirabayashi et al, , 2021Yamazaki et al, 2018;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dams present are not only unpassable obstacles for migratory species but also affect the hydrological dynamics and water quality characteristics that can potentially affect a wide range of freshwater organisms (Poff & Zimmerman, 2010). The most significant cumulative hydrological alterations of dams in the Amazon are in the frequency and duration of flow pulses (Timpe & Kaplan, 2017), with large dams in certain subbasins of the Amazon having already altered downstream river flow amplitude by up to 3 orders of magnitude (Chaudhari & Pokhrel, 2022). However, the Amazon still contains many free‐flowing rivers (FFR) with a recent study documenting the Amazon River as the longest remaining FFR from source to outlet globally (Grill et al, 2019).…”
Section: Introductionmentioning
confidence: 99%